Basic synonyms in English you should know - Fanha Martins, Hélder (2017)
Synonyms are words that are similar or have a related meaning, to another word. They can be lifesavers when you want to avoid repeating the same word over and over. Also, sometimes the word you have in mind might not be the most appropriate word, which is why finding the right synonym can come in handy. (...)